Comparing the Long Term Mid-IR Variability of Different AGN Types - Houston, Lilianna (Tufts Archival Research Center, 2021)
We investigate the variability of mid-IR selected Active Galactic Nuclei of different classes. We use statistical methods to assess the variability of different AGN types. We examine individual high variability sources and study the follow-up spectrum of one such source. By studying the variability of multiple AGN types, we gain insight into the differing geometric structure and emission of these objects.; An Honors Thesis for the Department of Physics and Astronomy